Sustained symptom reduction in complex regional pain syndrome with a novel home-based virtual reality program: a pilot study - Fontenot, Miles R.; Curatolo, Michele; Stacey, Brett R.; Flor, Herta; Hoffman, Hunter G. (Frontiers in neurology, 2025)
BackgroundComplex regional pain syndrome (CRPS) often leads to limb disuse, pain catastrophizing, and depression. While physical movement of CRPS affected limbs is essential for improvement, pain discourages movement. Home-based virtual reality (VR) interventions may reduce movement-related pain, improve adherence, and promote sustained symptom reduction.MethodsIn this exploratory pilot study, seven patients with CRPS completed a 4-month home-based VR program integrating three treatment modules (1) embodied cyberhands VR physical movement treatment, (2) VR-mindfulness-based-stress-reduction, and (3) VR-pain-neuroscience-education. The primary outcomes were patient-reported global impressions of change in CRPS-related pain and physical ability. Secondary outcomes included central sensitization, cold sensitivity, depression, pain catastrophizing, and upper-limb function.ResultsOn the primary outcome global impression of change measures, six of seven patients reported sustained improvement in CRPS-related pain and physical ability, with three reporting being “much” or “very much” improved at 4 months. Gains were maintained at 1-year follow-up. Secondary outcomes showed significant improvements at 4 months: central sensitization (CSI: 46.7 ± 11.97 to 38.4 ± 11.53), cold pain threshold (27.12 °C ± 3.89 to 24.56 °C ± 5.56), depression (CES-D: 23.0 ± 11.27 to 15.6 ± 8.85), pain catastrophizing (PCS: 24.3 ± 11.06 to 15.1 ± 9.67), and upper-limb function (QuickDASH: 47.7 ± 20.43 to 34.8 ± 17.47). Improvements were sustained at 1-year follow-up. No serious adverse events occurred, and study adherence was 100%.ConclusionResults provide preliminary evidence that a home-based VR program may produce sustained improvements in CRPS-related pain, physical ability, and associated symptoms. Larger randomized controlled trials are recommended.Clinical trial registrationThe study was registered on September 21, 2024, with the identifier number NCT05888142.
Gesehen am 17.02.2026